Bahasa Isyarat Kata Kolok Ditinjau Dari Segi Etnografi - Dede Fitriansyah; Faiz Noormiyanto (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to examine the Kata Kolok Sign Language used by the deaf community in Desa Bengkala, Bali, through an ethnographic approach. This sign language is not merely a tool of communication, but also reflects cultural values, social structure, and the collective identity of the community. The methods employed include observation, interviews with various informants (Kolok residents, general community members, interpreters, and historians), as well as visual documentation. The findings show that the Kata Kolok Sign Language is widely used, not only by deaf residents but also by the general community, including children from an early age. This sign language has become an integral part of daily life, encompassing the home environment, markets, schools, and customary activities. The open and inclusive communication structure indicates that the presence of the Kata Kolok Sign Language strengthens relationships among residents and helps the community accept differences. In this context, sign language functions not only to convey messages, but also as a cultural bridge that reinforces intergroup relationships within the village.